Corporate Inversions and Governance - Cortes, Felipe; Gomes, Armando; Gopalan, Radhakrishnan (Journal of Financial Intermediation, 2021)
Whether an inversion is associated with weaker firm governance is an open empirical question. While many inversions happen to countries that offer weaker protection to minority shareholders than the U.S., most firms that invert continue to be treated by the SEC as an “U.S. issuer”, and thus, their shareholders benefit from the full protection offered by the U.S. Federal Securities Laws. Our analysis shows that firms that invert exhibit an increase in their stock illiquidity, information asymmetries, and a decrease in their institutional shareholdings, indicating a weaker market-based governance following the inversion. Executives also receive a smaller proportion of equity-based compensation and their wealth is less sensitive to stock prices following the inversion. Thus, despite enjoying the full protection of federal securities laws, investors perceive inverted firms to have weaker governance relative to comparable U.S. firms.